Elite athletes refine their internal clocks - Chen, Y.-H.; Cesari, P. (Motor control, 2015)
Evaluating time properly is crucial for everyday activities from fundamental behaviors to refined coordinative movements such as in sport playing. Lately the concept of the existence of a unique internal clock for evaluating time in different scales has been challenged by recent neurophysiology studies. Here we provide evidence that individuals evaluate time durations below and above a second based on two different internal clocks for sub- and suprasecond time ranges: a faster clock for the subsecond range and a slower one for suprasecond time. Interestingly, the level of precision presented by these two clocks can be finely tuned through long-term sport training: Elite athletes, independently from their sport domains, generate better time estimates than nonathletes by showing higher accuracy and lower variability, particularly for subsecond time. We interpret this better time estimation in the short durations as being due to their extraordinary perceptual and motor ability in fast actions. ABSTRACT FROM AUTHOR